Pengaruh Sikap Merek dan Persepsi Kualitas terhadap Keputusan Pembelian dengan Citra Merek sebagai Variabel Mediasi - Sari, Junia Anggita Sari Anggita (Jurnal Ilmiah Poli Bisnis, 2022)
The Influence of Brand Attitude and Perception of Quality on Purchase Decisions with Brand Image as a Mediation Variable (Case Study of Nivea Products in Yogyakarta City). This study aims to determine the influence of Brand Attitude (SM), Perceived Quality (PK), Brand Image (CM) on Purchase Decisions (KP) on Nivea Products in Yogyakarta City. The sample of this research is 80 respondents. The sampling technique used was Accidental Purposive Sampling. The data used is primary data, with the source of data obtained from the method of distributing questionnaires. Data analysis in this study used multiple regression. The results show that 1) Brand Attitude has a positive and significant effect on Purchase Decisions, 2) Quality Perception has a positive and significant effect on Purchase Decisions, 3) Brand Image has a positive and significant effect on Purchase Decisions, 4) Brand Attitude has a positive and significant effect on Image. Brand, 5) Perception of Quality has a positive and significant effect on Brand Image, 6) Brand Image on Purchase Decision with Brand Image as a mediating variable has a positive effect and 7) Perception of Quality on Purchase Decision with Brand Image as a mediating variable has a positive effect.